Endoglin Wild Type and Variants Associated With Hereditary Hemorrhagic Telangiectasia Type 1 Undergo Distinct Cellular Degradation Pathways - Gariballa, Nesrin; Kizhakkedath, Praseetha; Akawi, Nadia; John, Anne; Ali, Bassam R. (Frontiers in Molecular Biosciences, 2022)
Endoglin, also known as cluster of differentiation 105 (CD105), is an auxiliary receptor in the TGF signaling pathway. It is predominantly expressed in endothelial cells as a component of the heterotetrameric receptor dimers comprising type I, type II receptors and the binding ligands. Mutations in the gene encoding Endoglin (ENG) have been associated with hereditary hemorrhagic telangiectasia type 1 (HHT1), an autosomal dominant inherited disease that is generally characterized by vascular malformation. Secretory and many endomembrane proteins synthesized in the Endoplasmic reticulum (ER) are subjected to stringent quality control mechanisms to ensure that only properly folded and assembled proteins are trafficked forward through the secretory pathway to their sites of action. We have previously demonstrated that some Endoglin variants causing HHT1 are trapped in the ER and fail to traffic to their normal localization in plasma membrane, which suggested the possible involvement of ER associated protein degradation (ERAD) in their molecular pathology. In this study, we have investigated, for the first time, the degradation routes of Endoglin wild type and two mutant variants, P165L and V105D, previously shown to be retained in the ER. Stably transfected HEK293 cells were treated with proteasomal and lysosomal inhibitors in order to elucidate the exact molecular mechanisms underlying the loss of function phenotype associated with these variants. Our results have shown that wild type Endoglin has a relatively short half-life of less than two hours and degrades through both the lysosomal and proteasomal pathways, whereas the two mutant disease-causing variants show high stability and predominantly degrades through the proteasomal pathway. Furthermore, we have demonstrated that Endoglin variants P165L and V105D are significantly accumulated in HEK293 cells deficient in HRD1 E3 ubiquitin ligase; a major ERAD component. These results implicate the ERAD mechanism in the pathology of HHT1 caused by the two variants. It is expected that these results will pave the way for more in-depth research studies that could provide new windows for future therapeutic interventions.